1999
DOI: 10.1063/1.124060
|View full text |Cite
|
Sign up to set email alerts
|

Temperature evolution of multiple tunnel junction devices made with disordered two-dimensional arrays of metallic islands

Abstract: The temperature behavior of multiple tunnel junction (MTJ) devices made with sub-5-nm gold islands is investigated. A smooth decrease of the Coulomb gap with increasing temperatures is observed. The critical temperature beyond which the Coulomb blockade effect is suppressed is found to change as a function both of the average size of the islands and of the size of the two-dimensional (2D) array of islands forming the MTJ. This latter property is attributed to the role of disorder in the 2D array. Results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…[2][3][4][5][6][7] In order to retain this current blockade effect up to high temperature, the charging energy E c ϭe 2 /2C, which is requested to allow an extra electron to flow through the single-electron device, must be larger than the thermal fluctuations k B T, with C the device capacitance, k B the Boltzmann constant, and T the temperature; Ϫe is the electrical charge of the electron (eϾ0).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] In order to retain this current blockade effect up to high temperature, the charging energy E c ϭe 2 /2C, which is requested to allow an extra electron to flow through the single-electron device, must be larger than the thermal fluctuations k B T, with C the device capacitance, k B the Boltzmann constant, and T the temperature; Ϫe is the electrical charge of the electron (eϾ0).…”
Section: Introductionmentioning
confidence: 99%
“…The factors of merit of MTJs for memory application are i) a total tunnel resistance in the M• range in order that the writing time related to the speed at which electrons can pass through the MTJ remain in the ns regime, and ii) a clear conservation of a Coulomb gap at operating temperature, which depends on the number, size and average charging energy of the islands forming the MTJ array. An experimental study of the temperature dependance of our disordered 2D MTJ arrays, supported by Monte Carlo simulations [5], showed that lateral patterning of the 2D arrays made the devices more robust against temperature. Figure 3 shows typical currentvoltage characteristics obtained on our 2D mxn Au MTJ arrays.…”
Section: Resultsmentioning
confidence: 81%
“…Above a critical temperature, slightly higher than 100 K, the gap is destroyed and a conductance can be measured at low voltage [5]. The 1 V Coulomb gap obtained for the MTJ at low temperature should enable high temperature operation of the LSEM, as well as a modulation of the MOS current by more than 3 decades between the "0" and "1" states.…”
Section: T=i8~' K /mentioning
confidence: 95%
See 2 more Smart Citations